THE INFLUENCE OF CAREER DEVELOPMENT AND COMPENSATION PERCEPTIONS OF COMPANIONSHIP ON WORK PRODUCTIVITY (Survey of District PKH Facilitators Tasikmalaya) - Iwan Sugianto; Muhammad Nurdin Yusuf; Melia Dianty (Nusantara Journal Of Management Business (NUMABI), 2023)
Study This aim For know The influence of career development on the work productivity of PKH assistants in Tasikmalaya Regency and The effect of compensation on the work productivity of PKH assistants in Tasikmalaya Regency Good in a manner Partial or simultaneous . Method Research used _ in study This is method descriptive qualitative . Data used in study This namely primary and secondary data . Withdrawal technique sample in study This using total sampling or saturated sampling , ie all element population chosen as sample that is Population in research This is whole all PKH Facilitators in Tasikmalaya Regency totaling 311 people Analysis tools used _ is in a manner especially qualitative _ formerly tested validity and reliability the data . Research results show that : H1 CR value at 2.320 P value at 0.020, results the showing CR values above 1.96 (9.718> 1.96) and P values below 0.05 (0.000 <0.05). this _ showing that hypothesis 1 (H1) is accepted because mark estimate obtained 0.162, meaning that with exists development career so will increase productivity Work district PKH assistant Tasikmalaya by 16.2% each One percent . hypothesis 2 (H2) is accepted because mark estimate For compensation obtained 0.160, that is that with exists compensation so will increase productivity Work of 16.0 % each One percent .